2018
DOI: 10.1002/suco.201800074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processed pozzolans on residual mechanical properties and macrostructure of high‐strength concrete at elevated temperatures

Abstract: Recently, use of processed pozzolans such as rice husk ash (RHA) and bagasse ash (BA) have been identified as promising mineral admixtures to produce HSC. As fire is considered one of the severe hazards to which a structure may be exposed, there is a requirement to evaluate the performance of HSC containing pozzolanic admixtures, namely, RHA and BA at elevated temperatures. In this study, the residual mechanical properties comprising, compressive and splitting tensile strength, compressive stress-strain respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In addition, while increasing demand on HPC is necessary and associated with construction industry growth and rapid global development, cement is the principal and most expensive component of HPC 11 . Therefore, environmental and economic factors played an important role in the utilization of pozzolanic minerals such as blast furnace slag, silica fume, and fly ash as well as better performance in terms of strength and durability by improving microstructure of concrete 12–17 . Not only supplementary cementitious minerals (pozzolanic minerals) but also inert minerals can provide better filling effect for cement paste, mortar and concrete, 18 and also these minerals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, while increasing demand on HPC is necessary and associated with construction industry growth and rapid global development, cement is the principal and most expensive component of HPC 11 . Therefore, environmental and economic factors played an important role in the utilization of pozzolanic minerals such as blast furnace slag, silica fume, and fly ash as well as better performance in terms of strength and durability by improving microstructure of concrete 12–17 . Not only supplementary cementitious minerals (pozzolanic minerals) but also inert minerals can provide better filling effect for cement paste, mortar and concrete, 18 and also these minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the issues of materials sustainability and environmental pollution accelerated by the concrete industry need to be addressed. Many researchers of our century have been looking for eco-friendly materials that can partially or totally replace cement in the mix with the aim of handling the raised concern on depletion of raw materials, atmospheric pollution, global warming and waste disposal [4]. However, such replacement should result in improved concrete properties in terms of strength and durability.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have been conducted to examine the properties of blended concrete at normal and elevated temperatures utilizing rice husk ash [6][7][8], palm oil fuel ash [9,10] and sugar cane bagasse ash [11,12] as admixtures in concrete production. The blended concrete was observed to perform better than normal concrete due to the presence of amorphous silica in the aforementioned synthetic pozzolanic materials [4,13]. Therefore, more materials with good properties can also be studied to save the purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The cooperation of lightweight aggregate (LWA) diminishes the demand of reinforcement as well as the size of the structural element, leading to the increased strength/weight fraction, fire resistance, and thermal properties. 3,4 Gesoglu et al 5 found spherical shape result in enhanced flowability including less block as well as lower internal friction for LWSCC. Hassan et al 6 validated the inverse correlation between LWA and the diameter of slump flow.…”
Section: Introductionmentioning
confidence: 99%